IIUM bus on campus monitoring system - Juhari, Muhammad Nur Zaki; Mansor, Hasmah (IEEE, 2016)
Malaysia has invested on public transport over the years to improve quality of leaving. Transportation has been identified as the key area in Malaysia’s government transformation programme. In Malaysia, many people still choose to use their own transport compared to public transport to travel. For efficient public transport service such as bus, real-time tracking/monitoring must be available apart from their fixed schedule. The objective of this project is to develop a low cost real-time IIUM bus on campus monitoring system. IIUM shuttle bus monitoring has been chosen as a pilot study which reflects the bigger picture of Malaysia’s bus system. In IIUM, students need to wait for the bus without any clue and this is such a waste of time. Thus, IIUM bus tracking system is proposed in this project where waiting time can be improved. Users can track the exact location of the bus therefore they can have better plan for their journey. Global positioning system technology has been used to send and receive the coordinate data to the server. A web server application has been developed to integrate the Global positioning system data to be presented on the map. At the end of the project, a website of real-time IIUM bus on campus monitoring system has been developed where users can monitor the exact location of the IIUM bus conveniently.